2010
DOI: 10.1016/j.ejogrb.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Spanish women's attitudes towards post-fertilization effects of birth control methods

Abstract: Objective: Some methods of family planning may occasionally work after fertilization or implantation. These effects may be important to some women. We explored Spanish women's attitudes towards these potential mechanisms of action of family planning methods.Study design: Cross-sectional study in a Spanish representative sample of 848 potentially fertile women, aged 18-49. Data were collected using a 30-item questionnaire about family planning. Logistic regression was used to identify variables associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Also, women who believe that human life begins at fertilization were less likely to consider the use of methods with postfertilization effects [15]. Similar results were found in another study carried out in the USA, where the majority of women believing that human life begins at fertilization reported that they would not use a method with postfertilization mechanisms [16].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Also, women who believe that human life begins at fertilization were less likely to consider the use of methods with postfertilization effects [15]. Similar results were found in another study carried out in the USA, where the majority of women believing that human life begins at fertilization reported that they would not use a method with postfertilization mechanisms [16].…”
Section: Introductionsupporting
confidence: 73%
“…In a previous study in Spain, this fraction was 45% for postfertilization effects and 57% for postimplantation effects [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Budgetary limitations precluded implementing the survey in more countries. Spain was not included because a similar survey had previously been conducted there [8].…”
Section: Methodsmentioning
confidence: 99%
“…A study carried out in several European countries found that contraceptive use, in general, was more common among single, highly educated women and those with several children [1]. In a study performed in Spain, beliefs about when human life begins was associated with women's potential decisions about using family planning (FP) methods with postfertilization and postimplantation effects [8].…”
Section: Introductionmentioning
confidence: 99%